2021
DOI: 10.3390/ijgi10080565
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Model for Integrating Indoor and Outdoor Network Data to Support Seamless Navigation Applications

Abstract: Spaces are continuous realms where human beings freely navigate, such as from indoor to outdoor and optionally to another indoor space. However, currently available data models to represent space for navigation do not entirely reflect this continuity of freedom and movement. Data conversion or complications in implementation hinder current approaches to link indoor space with outdoor space due to the variety of present data models. Furthermore, this representation of indoor–outdoor connection becomes oversimpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This will also allow opportunities for utilizing the model in multi-modal navigation applications. This case of transitional spaces may be represented as a graph, portraying the connection of an indoor to an outdoor network through an intermediate space having its own navigation paths (Claridades and Lee, 2021).…”
Section: Figure 7 Results Of the Routing Implementationmentioning
confidence: 99%
“…This will also allow opportunities for utilizing the model in multi-modal navigation applications. This case of transitional spaces may be represented as a graph, portraying the connection of an indoor to an outdoor network through an intermediate space having its own navigation paths (Claridades and Lee, 2021).…”
Section: Figure 7 Results Of the Routing Implementationmentioning
confidence: 99%
“…We attempted not to visualize the total duration of tourists' stays, which tends to be affected by the characteristics of buildings, but to tally the number of visitors. When a user is indoors, GPS accuracy data values decrease because of ceilings and walls [39,40]. Our framework detects a set of locations of staying using GPS horizontal accuracy data and Th indoor and abstracts them by calculating a center point of the minimum bounding box.…”
Section: Abstract the Locations Of Stayingmentioning
confidence: 99%
“…Indoor spaces are not isolated systems because space is fundamentally continuous despite being expressed separately across data and applications [30]. However, studies have demonstrated seamless indoor-outdoor navigation in different scenarios and different models of indoor-outdoor space integration [1,31,32]. However, as agents traverse from outdoor to indoor space, the navigation network is uniformly expressed across these demonstrations.…”
Section: Related Literaturementioning
confidence: 99%